Investigation of Dairy Cattle Concentrate Quality, Traceability & Handling Practices Adopted by Farmers – A Case Study Conducted in Sri Lanka - Wilamune, N. H. B.; Jayasignhe, M. A.; Chinthaka, U. G. S.; Silva, V.; Gunawardena, S. N. A.; Bodaragama, S. G.; Samarasinghe, C. H. (International Journal of Advanced Engineering Research and Science, 2021)
This study was done in selected dairy farms in Central Province of Sri Lanka. As the Stage 1, 67 farms were selected and type, quality, traceability and farm level handling practices of different dairy cattle concentrates were identified. Analyzed results were; scale of dairy farming and farming method used, dairy cattle concentrate types used, product information & packaging and handling practices. Major findings were; average number of cows per farm was 3.1, concentrate types identified were coconut oil cake and formulated dairy cattle concentrate, 75.9% of the coconut oil cake products on the market had an unknown origin, all the coconut oil cake products had no product details and none of the farmers used total mix rations to feed their animals. For the Stage 2, 64 dairy farms were selected. Moisture content of the dairy cattle concentrates were analyzed with respect to the storage method and they were statistically analyzed. Out of all the farms, 37.5% used coconut oil cake and 62.5% used formulated dairy cattle concentrates as their dairy cattle concentrate. In coconut oil cake uses, there was a significant difference (P<0.05; P=0.003) of moisture content between products stored on pallets without sealing well and well-sealed products on pallets and there was no significant difference (P>0.05; P=0.159) between the moisture contents with respect to the storing methods used to store formulated dairy cattle concentrates. Hence, this study provides an indication that coconut oil cake requires careful sealing and storing since it has a greater tendency to absorb atmospheric moisture.